Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

L’ambition territoriale dans le dossier de la santé en français - Gilbert, Anne; Lefebvre, Marie; Bouchard, Louise (Francophonies d’Amérique, 2010)
Dix ans se sont écoulés depuis le jugement Montfort, qui consacrait l’Hôpital comme une composante essentielle de la vitalité des communautés francophones en situation minoritaire. Jusqu’à quel point cette reconnaissance du droit à un service en français, accessible dans des établissements localisés dans les milieux dans lesquels la minorité évolue, a-t-elle mené à une ambition plus territoriale chez les intervenants francophones ? L’analyse des propos tenus par 38 participants à un exercice de cartographie conceptuelle sur l’avenir des services de santé en français en Ontario révèle qu’ils ne s’aventurent pas très loin sur le terrain des modalités de l’édification d’un véritable territoire francophone en santé. L’institution est évoquée, mais davantage comme un projet appartenant à un horizon lointain que comme un enjeu actuel. En guise de conclusion, les auteures se sont interrogées sur les effets d’une telle vision sur l’avenir des services de santé en français.

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)